2018
DOI: 10.1139/cjz-2017-0117
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative approaches to sensory information encoding by bat noseleaves and pinnae

Abstract: The biosonar systems of horseshoe bats (Rhinolophidae) and Old World round leaf-nosed bats (Hipposideridae) incorporate a pervasive dynamic at the interfaces for ultrasound emission (noseleaves) and reception (pinnae). Changes in the shapes of these structures alter the acoustic characteristics of the biosonar system and could hence influence the encoding of sensory information. The focus of the present work is on approaches that can be used to investigate the hypothesis that the interface dynamic effects sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In addition to the static geometric complexity of the biosonar periphery, there are dynamic changes to the shapes of the noseleaves and pinnae as a result of fast muscular actuation [19][20][21][22]. These active deformations add a dynamic dimension to the encoding of sensory information, which would be a novel functional principle for technical sensors [23][24][25][26][27]. Results from numerical beampattern predictions have indicated that noseleaves have an effect on the shape of the emission patterns [15,17,28].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the static geometric complexity of the biosonar periphery, there are dynamic changes to the shapes of the noseleaves and pinnae as a result of fast muscular actuation [19][20][21][22]. These active deformations add a dynamic dimension to the encoding of sensory information, which would be a novel functional principle for technical sensors [23][24][25][26][27]. Results from numerical beampattern predictions have indicated that noseleaves have an effect on the shape of the emission patterns [15,17,28].…”
Section: Introductionmentioning
confidence: 99%
“…These capabilities allow the bats to thrive in dense vegetation and offer valuable insights in technical sensing paradigms, sonar or otherwise. The significance of bat biosonar for engineering has been published elsewhere [16], [17]. In addition to gaining research experience, the IRES students participated in seminars and field trips during 8-week period in China.…”
Section: China Iresmentioning
confidence: 99%